Responses and adverse effects of carboplatin-based chemotherapy for pediatric intracranial germ cell tumors - Suntae Ji; Hee Won Chueh; Ju Youn Kim; Su Jin Lim; Eun Joo Cho; Soo Hyun Lee; Keon Hee Yoo; Ki Woong Sung; Hong Hoe Koo (Korean Pediatric Society, 2011)
PurposeCisplatin-based chemotherapy has been commonly used for the treatment of intracranial germ cell tumors (IC-GCTs). However, this treatment exhibits some adverse effects such as renal problems and hearing difficulty. Carboplatin-based chemotherapy was administered to pediatric patients with IC-GCTs from August 2004 at the Samsung Medical Center. In this study, we assessed the responses and adverse effects of carboplatin-based chemotherapy in pediatric IC-GCTs patients according to the risk group, and compared the results with those of the previous cisplatin-based chemotherapy.MethodsWe examined 35 patients (27 men and 8 women) diagnosed with IC-GCTs between August 2004 and April 2008 and received risk-adapted carboplatin-based chemotherapy at the Samsung Medical Center. Patients were divided into either low-risk (LR) or high-risk (HR) groups and a retrospective analysis was performed using information from the medical records.ResultsAlthough hematological complications were common, hearing difficulties or grade 3 or 4 creatinine level elevation were not observed in patients who underwent carboplatin-based chemotherapy. The frequency of febrile neutropenia did not differ between the risk groups. The overall survival was 100% and event-free survival (EFS) was 95.7%. The EFS rate was 100% in the LR group and 90% in the HR group, respectively.ConclusionDespite their common occurrence in high-risk patients, no lethal hematological complications were associated with carboplatin-based treatment. The current carboplatin-based chemotherapy protocol is safe and effective for the treatment of pediatric patients with IC-GCTs.